Beyond the smiley face: applications of structural DNA nanotechnology. (1st January 2018) - Arora, Aakriti Alisha; de Silva, Chamaree
ABSTRACT: Since the development of DNA origami by Paul Rothemund in 2006, the field of structural DNA nanotechnology has undergone tremendous growth. Through DNA origami and related approaches, self-assembly of specified DNA sequences allows for the 'bottom-up' construction of diverse nanostructures. By utilizing different sets of small 'staple' DNA strands to direct the folding of a long scaffold strand in diverse ways, DNA origami has particularly been incorporated into a variety of prototypical applications beyond the two-dimensional (2D) smiley face. In this review, the basis of DNA nanotechnology, methods of self-assembly, and Rothemund's DNA origami breakthrough are discussed first. Next, some of the most promising applications of structural DNA nanotechnology since 2006 are summarized. These include utilizing DNA origami as a tool for creating 3D nanostructures (including DNA bricks), as well as structural (ligand capsid binding, viral capsid binding, DNA NanoOctahedron, DNA mold, photonic devices, energy transfer units), and dynamic (DNA box-with-lid, DNA nano-robot, DNA barges, amphipathic DNA structures, DNA nanocircuits) applications of DNA origami.